Build the life you want : the art and science of getting happier [large type] - Brooks, Arthur C., 1964-; Winfrey, Oprah (Random House Large Print, 2023)
"Arthur C. Brooks and Oprah Winfrey combine their decades of experience studying happiness from every angle to show readers how to improve their lives right now, instead of waiting for the outside world to change. They offer a research-based work plan that shows the reader how to manage their emotions so they no longer control their outlook and behavior; turn life's inevitable difficulties and challenges into opportunities for growth; strengthen their family ties by managing expectations and building trust; create and preserve deep and lasting friendships at any age; develop an approach to work that fits their life and brings satisfaction; and find inner peace with a spiritual practice" --